Kerjasama Guru Dan Orang Tua Guna Meningkatkan Hasil Belajar Sosiologi Siswa Kelas XI Di SMA Pontianak - Yanti, M. M. (UNIVERSITAS TANJUNGPURA, 2013)
This study of the Cooperation Teachers And Parents To Improve Learning Outcomes XI Sociology class in High School in Pontianak. Aims to improve learning outcomes in sociology. This research uses descriptive method. The results showed that; (1). Collaboration Teachers in improving student learning outcomes are relatively good.(2). The role of parents in improving student learning outcomes are relatively well.perform, (3). Collaboration teachers and parents relatively well cooperation, (4). The results of learning indicate of 75.7. From these results we can conclude cooperation teachers and parents relatively well handed.Key Words: Cooperation Teachers and Parents, Learning Outcomes.